QUALITY OF INSTRUCTION IN UP COMING UNIVERSITIES IN THE CASE OF RONGO UNIVERSITY, KENYA - Omito, Ouma (International Journal of Research -GRANTHAALAYAH, 2018)
The study aimed at establishing the quality of instruction to Rongo University students with the aim of producing productive university graduates in all sectors of the world’s economy. To achieve this, the researcher formulated one specific objective: to investigate the quality of instruction offered to students by Rongo University’s lecturers. The study used survey design with well-constructed questionnaires. The target population was 30 regular students of Bachelor of Education (Arts) who were training to be business studies teachers in secondary schools in Kenya. A sample size of 28 respondents was reached at by the use of Krajcie and Morgan (1970) table. Simple random sampling was used to pick the respondents. Descriptive statistics such as frequencies and percentages were used to analyze data. The study found that teaching in upcoming universities lacked follow ups, right technology and adequate assignments to students. The study also found that Rongo University was not doing enough to migrate into the digital space since the main method of instruction was face to face and at the same time the available university library did not cater fully for the library needs of students who were outside the main campus. The respondents for this study who were studying outside the main campus relied on internet from their mobile phones as the main source of their reading materials. The study recommended robust reforms that could bring in quality to the ever escalating numbers of higher learning institutions in the world.